Pengaruh Model Pembelajaran Think Pair Share (TPS) Berbantu Media Edpuzzle terhadap Hasil Belajar Siswa Kelas XI MIPA - Putri Zahra Deliano (Journal on Education, 2023)
The learning model that can be an innovation in learning to support the achievement of learning objectives is cooperative learning with the Think Pair Share type. The application of this model certainly needs to be supported by the use of media which will have a good impact on student learning outcomes. One of the media that can be used is Edpuzzle. This study aims to determine the effect of Think Pair Share (TPS) learning on student learning outcomes in class XI MIPA SMAS Kartika XIX-1 Bandung, especially in the matter of the respiratory system. The method used is Quasi Experimental with a non-equivalent group research design. The populations of the study were students of class XI MIPA at SMAS Kartika XIX-1 Bandung. Two classes were taken, XI MIPA 2 and XI MIPA 3 using purposive sampling technique. Analysis of research data obtained an average student learning outcomes in the experimental class with an average pretest score of 36.29, a posttest of 65.29 with an N-Gain value of 0.45 in the medium category. Hypothetical data using the Man Whitney test shows the value of Sig. 0.04 < 0.05 indicates that H1 is accepted. Based on the results of the study it can be concluded that the Think Pair Share (TPS) learning model assisted by Edpuzzle media has a positive effect on student learning outcomes in the respiratory system material and further enhances student learning outcomes.